The Co-Development of Science, Math, and Language Interest Among Spanish and Finnish Secondary School Students - Sainz, Milagros; Upadyaya, Katja; Salmela-Aro, Katariina (Frontiers in Education, 2021)
The present two studies with a 3-year longitudinal design examined the co-development of science, math, and language (e.g., Spanish/Finnish) interest among 1,317 Spanish and 804 Finnish secondary school students across their transition to post-compulsory secondary education, taking into account the role of gender, performance, and socioeconomic status (SES). The research questions were analyzed with parallel process latent growth curve (LGC) modeling. The results showed that Spanish students’ interest in each domain slightly decreased over time, whereas Finnish students experienced an overall high and relatively stable level of interest in all domains. Further, boys showed greater interest in math and science in both countries, whereas girls reported having a greater interest in languages. Moreover, Spanish and Finnish students with high academic achievement typically experienced high interest in different domains, however, some declines in their interest occurred later on.